Efeito da acupuntura nos transtornos de humor e memória induzidos por neuropatia periférica, associada ou não ao tratamento com gabapentina - Ramires, Caroline Cadore (2019)
Peripheral neuropathies cause chronic pain, which are associated with cognitive, memory and emotional changes, such as depression and anxiety. These factors are related to the expression of brain markers, such as brain-derived neurotrophic factor (BDNF). The treatment of chronic pain often occurs with the use of drugs. However, treatments such as acupuncture may be an effective therapy in this problem, whether or not associated with existing drugs. Thus, the aim of this study was to verify the effect of acupuncture on acupuncture SP6 (Sanyinjiao), alone or in combination with daily gabapentin treatment, on hypersensitivity, as well as mood and memory disorders induced by partial sciatic nerve ligation (LPNC) in mice. The procedures were previously approved by the ethics committee of UNIPAMPA (n. 038/2017) and performed in stages: 1) False Operated (FO), Operated (OP - with LPNC) and Acupuncture (LPNC + treatment with SP6) groups n=8. The SP6 group was treated three times a week. The mechanical and thermal hypersensitivity tests were evaluated daily. After 5 and 10 treatments with acupuncture, the animals were evaluated in the tail suspension test (TSC), pluz maze (PM) and inhibitory avoidance (EI), and their hippocampi removed for BDNF analysis by ELISA. In group 2, groups with gabapentin (GB - 10mg / kg, oral), sub - effective dose of 5mg / kg (GBP1 / 2) and sub - effective dose associated with acupuncture (GBP1 / 2 + SP6) were added. After 10 treatments with acupuncture, the animals were evaluated in the TSC, forced swimming test (TNF), PM and EI, and their hippocampus removed for BDNF analysis. Acupuncture reduced mechanical and thermal hypersensitivity, reduced immobility time in TSC, and increased LAI latency time after 30 minutes of training with 5 and 10 treatments induced by LPNC. Still, with 10 treatments, there was an increase in the latency time in IE after 24 hours of training. It can be verified that in both evaluated times, the SP6 increased the hippocampal BDNF levels. Subsequently, we verified reduction of mechanical hyperalgesia in the groups GB, GBP1/2 and GBP1/2+SP6. Furthermore, the groups treated with GB and GBP1/2+SP6 reduced only the time of immobility in TSC and TNF. None of the additional groups modified the reduction of BDNF induced by LPNC. No statistical differences were observed between groups SP6 and GBP1/2+SP6. We can conclude that acupuncture was effective in reducing hyperalgesia and problems such as depression and memory disorders associated with peripheral neuropathy. The association of GB did not contribute to improve the effect of acupuncture in any of the observed analyzes, still interfering in the results of aversive memory and BDNF levels.